Solvent and non-solvent selection for the chemical recycling of waste polyethylene (PE) and polypropylene (PP) metallized film packaging materials - Gorre, Regino C. Jr
Multilayer plastic packaging wastes are difficult to recycle due to its different layers of materials which limit the quality of the recycled product. These wastes accumulate in our landfills and end up polluting our oceans. A solvent and non-solvent selection method for the chemical recycling through selective dissolution and precipitation of multi-component waste metallized film wrapper is studied to recover PE, PP, and the metal film separately. Pre-selection of solvent for dissolution and non-solvent for precipitation is based on the similarity and compatibility of polymer and solvent molecules measured in terms of solubility parameter and calculated using group contribution approach through Hoftyzer and Van Krevelen method. Toxicity, cost, and availability of solvent are also considered on the selection. A Hansen sphere model and relative energy difference graph is developed for the prediction of polymer solubility in which p-cymene, a low-cost and naturally derived solvent is chosen as solvent and acetone as non-solvent. PE was first recovered through dissolution at a given temperature, followed by precipitation. PP which remained undissolved together with the metal film was extracted through the same technique but with different dissolution temperature. FTIR spectra of the recovered polymers showed similarity compared to virgin PE and PP films. The melting point of the recovered PE and PP using p-cymene determined in the DSC curves were 107.37°C and 164.55°C, respectively. Furthermore, the simplicity of the process, high recovery yield obtained, and application of p-cymene would make the recycling economical and environment-friendly